Prognostic nutrition index predicts short-term surgical complications in patients with rectal cancer after laparoscopic surgery - Xu, Fengming; Meng, Cong; Yang, Zhengyang; Li, Haoze; Gao, Jiale; Sun, Liting; Zhang, Xiao; Wei, Qi; Wu, Guocong; Yao, Hongwei; Zhang, Zhongtao (Frontiers in Surgery, 2022)
Abstract Purpose: Surgical complications following laparoscopic rectal cancer surgery remain a major clinical problem. The prognostic nutritional index (PNI) is reportedly associated with postoperative outcomes. We aimed to evaluate the correlation between PNI and short-term surgical complications in patients with rectal cancer after laparoscopic surgery. Methods: The prospective clinical data of 225 patients with rectal cancer receiving laparoscopic surgery between January 2021 and April 2022 were analyzed. The cut-off values and diagnostic accuracy of PNI preoperatively and on postoperative day (POD) 1 were determined using receiver operating characteristic (ROC) curves. Univariate and multivariate analyses were performed to identify clinical characteristics and risk factors for surgical complications. Results: In total, 81 (36.0%) patients developed surgical complications. The optimal cut-off value for preoperative PNI was 40.15, and that for PNI on POD 1 was 35.28. The DeLong test found no statistically between–group difference in the area under the ROC curve (P=0.598). Multivariate analysis identified that a preoperative PNI ≤ 40.15 (odds ratio [OR]: 2.856, 95% confidence interval [CI]: 1.287–6.341, P= 0.010) and PNI on POD 1 ≤ 35.28 (OR: 2.773, 95% CI: 1.533–5.016, P=0.001) were independent risk factors for surgical complications. Patients with a preoperative PNI ≤ 40.15 or PNI on POD 1 ≤ 35.28 were more likely to have surgical complications after laparoscopic surgery for rectal cancer (61.1% vs. 31.2%, P=0.001; 53.0% vs. 28.9%, P=0.001). Conclusions: Preoperative and POD 1 PNI were independent predictors of surgical complications after laparoscopic surgery for rectal cancer.